Peternakan Kambing untuk Wisata Pendidikan dan Rekreasi: Hibah Pemberdayaan Masyarakat Pemula di El-Farm - Hermawan, Hary; Mahiswara, Amelia Lintang; Afif, Fuadi; Hendrajaya, Agnestasya Monica Putri; Girsang, Pitta Theresya Br (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
Goat Farming for Educational and Recreational Tourism Purposes: Grant for Empowering Beginner Communities at El-Farm The outcomes of the Community Service activity carried out at El Farm mostly went as planned. It has been demonstrated that the community's understanding of Formulation and development of livestock-based tourism products, Preparation and packaging of educational tourism packages, and Enhancement of understanding of marketing and tourism services has improved due to the training activities followed by intensive mentoring. The achievement is visible in the increase in pre-test and post-test scores, which exceeds 50%. Trial runs of tourism packages have also been undertaken by inviting tourists, including Sekolah Tinggi Pariwisata AMPTA students and faculty members from other universities, as well as trial activities such as the village painting competition and a lecture at El Farm.This project has received strong support from various stakeholders, including the Village Government, the Tourism Department, Higher Education Institutions, and several business entities. As a suggestion for future activities, it is suggested that more intense mentorship be continued, including assessing activity accomplishments and the long-term impact of the Community Service Program on partners.